Kimura's disease: a neoplasm mimicking, a rare benign form of chronic inflammatory disorder - Harley Septian; Made Widhi Asih; Nyoman Srie Laksminingsih; Anak Agung Ayu Ngurah Susraini (Intisari Sains Medis, 2021)
Background: Kimura's Disease (KD) is a benign, rare form of chronic inflammatory disease of unknown origin, almost exclusively found in Asian males in their second to fourth decades of life. This rare condition is mostly present as soft tissue mass consists of multiple painless solitary subcutaneous nodules mostly localized in the head and neck region, with coexisting lymph node enlargement and eosinophilia. This case study aims to describe Kimura's Disease (KD) characteristics and give an insight into the role of Computed Tomography (CT) scan in identifying KD and its imaging characteristics.Case Presentation: We reported a case of an Asian man with a history of 18 years left-sided painless facial mass, gradually increase in size with no history of hoarseness, epistaxis, previous facial mass or malignancy, and familial malignancy. CT scan findings showed an inhomogeneous contrast enhancement soft tissue mass located on the left parotid-submandibular region with multiple neck lymphadenopathy and left parotid gland involvement. Eosinophilia was found persistently in the laboratory outcomes, and this mass had been confirmed with histological findings consistent with KD features.Conclusion: Recognizing the characteristics of KD and the imaging findings on Ultrasound and CT-scan as accessible and first-line diagnostic tools, might help in facilitating the diagnosis, making a decision and sparing the patient from unnecessary and harmful procedures.